Strongly coordinating mediator enables single-step resource recovery from heavy metal-organic complexes in wastewater - Wei Shi; Jiayi Li; Fei Gao; Lijun Meng; Xiao Su; Zhiwei Wang (Nature Communications)
Abstract Heavy metals complexed with organic ligands are among the most critical carcinogens threatening global water safety. The challenge of efficiently and cost-effectively removing and recovering these metals has long eluded existing technologies. Here, we show a strategy of coordinating mediator-based electro-reduction (CMBER) for the single-step recovery of heavy metals from wastewater contaminated with heavy metal-organic complexes. In CMBER, amidoxime with superior coordinating abilities over traditional ligands is immobilized by an amidoximation reaction onto a flow-through electrode that concurrently functions as a filtration device. This unique process spontaneously captures heavy metal ions at the -N-OH and -NH2 groups of the amidoxime from their complexes without external energy input (ΔG of amidoxime mediator with Cu(II): −6.59 eV), followed by direct in situ electro-reduction for metal recovery. The reduction of captured Cu(II) to Cu(0) regenerates the amidoxime’s active sites, enabling continuous capture of Cu(II). Operating at a voltage of 3 V and a water flux of 250 L m−2 h−1, the CMBER system achieves a Cu(II) recovery rate of 97.6% and demonstrates an energy efficiency of 340.1 g kWh−1. This energy efficiency significantly outperforms existing technologies, showing a nearly fivefold improvement. CMBER creates a new dimension for cost-effective resource recovery and water purification.